2023
DOI: 10.3389/fonc.2023.1127086
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal analysis of genome-wide methylation, copy number aberrations, and end motif signatures enhances detection of early-stage breast cancer

Abstract: IntroductionBreast cancer causes the most cancer-related death in women and is the costliest cancer in the US regarding medical service and prescription drug expenses. Breast cancer screening is recommended by health authorities in the US, but current screening efforts are often compromised by high false positive rates. Liquid biopsy based on circulating tumor DNA (ctDNA) has emerged as a potential approach to screen for cancer. However, the detection of breast cancer, particularly in early stages, is challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 77 publications
(114 reference statements)
1
4
0
Order By: Relevance
“…The low sensitivity for detecting ctDNA signal in breast and gastric samples was consistent with our previous study that validated the performance of SPOT-MAS in these two types of samples ( 17 ). Our findings are in line with previous studies showing low levels of ctDNA shedding by early-stage gastric and breast tumors ( 4, 15, 21 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The low sensitivity for detecting ctDNA signal in breast and gastric samples was consistent with our previous study that validated the performance of SPOT-MAS in these two types of samples ( 17 ). Our findings are in line with previous studies showing low levels of ctDNA shedding by early-stage gastric and breast tumors ( 4, 15, 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…To improve the detection sensitivity of ctDNA, MCED screening methods tend to use high-depth sequencing, making it economically impractical for population-wide screening 10,19 . To address these limitations, we have recently developed a multimodal method, known as Screening for the Presence Of Tumor by Methylation And Size (SPOT-MAS), to simultaneously detect five common types of cancer, including liver, breast, colorectal, gastric, and lung cancer, and predict the tissue origin of cancer signal 17,20,21 . By integrating cost-effective shallow sequencing and advanced machine learning, SPOT-MAS was trained and validated on a large cohort of 2,288 participants, including 738 nonmetastatic cancer patients and 1,550 healthy controls, achieving a sensitivity of 72.4% at 97.0% specificity and an accuracy of 70.0% for tumor-of-origin (TOO) prediction 21 .…”
Section: Introductionmentioning
confidence: 99%
“…WGBS is primarily used to measure DNA methylation across the entire genome but can also be used reliably in detecting copy number variations (CNVs) 24 , 25 . In this study, we conducted copy number analysis from WGBS data, which revealed CNVs in recurrent tumors consistent with known copy number alterations in various primary tumor types studied (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study of SPOT-MAS, we have demonstrated that the integration of ctDNA methylation and fragmentomic features can significantly improve the early detection of colorectal cancer ( Nguyen et al, 2022a ) and breast cancer ( Pham et al, 2023 ). Here, we expanded the breadth of ctDNA analyses by adding two sets of features including DNA copy number and EM into SPOT-MAS to maximize cancer detection rate and identify TOO.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to address the challenges of early cancer detection, we have developed a multimodal approach called SPOT-MAS (screening for the presence of tumor by DNA methylation and size). This assay was previously applied to cohorts of colorectal ( Nguyen et al, 2022a ) and breast cancer patients ( Pham et al, 2023 ) and demonstrated ability for early detection of these cancers at high sensitivity across different cancer stages and patient age groups. In this study, we aimed to expand our multimodal approach, SPOT-MAS, to comprehensively analyze methylomics, fragmentomics, DNA copy number, and end motifs (EMs) of cfDNA and evaluate its utility to simultaneously detecting and locating cancer from a single screening test.…”
Section: Introductionmentioning
confidence: 99%